The predictive value of the ratio of the product of neutrophils and hemoglobin to lymphocytes in non‐muscular invasive bladder cancer patients with postoperative recurrence. Issue 8 (29th June 2021) - Zhao, Ruining; Shan, Jiahao; Nie, Lihong; Yang, Xiaobo; Yuan, Zhongyu; Xu, Haoran; Liu, Ziyang; Zhou, Xiaojie; Ma, Wenzhuo; Shi, Hongbin
Abstract: Purpose: The purpose of this study was to explore the predictive value of the ratio of the product of neutrophils and hemoglobin to lymphocytes (NHL) in patients with non‐muscular invasive bladder cancer (NMIBC). Materials and Methods: We retrospectively collected clinical and pathological data of patients with NMIBC who underwent transurethral resection of bladder tumor (TURBT) at our hospital between 2013 and 2018. The ratio of neutrophils to lymphocytes (NLR), the Systemic Immune Inflammation Index (SII), and NHL were obtained based on routine blood settlement within a week before surgery. The receiver operating characteristic curve was used to determine the optimal cutoff value of each index, and different groups were grouped accordingly. Kaplan‐Meier survival curve and Cox regression model were used to study the factors affecting the prognosis of NMIBC patients. Results: There was significant difference in recurrence‐free survival (RFS) rate between the high NLR group and the low NLR group, the high SII group and the low SII group, and the high NHL group and the low NHL group. Cox univariate regression analysis showed that tumor number, tumor size, tumor pathological grade, tumor pathological stage, NLR, SII, and NHL were related to postoperative RFS in patients with NMIBC. The tumor number, tumor pathological grade, SII, and NHL were independent predictors of RFS in multivariate analysis. Conclusions: The preoperative clinical inflammatory indexes NLR, SII, and NHL have certain predictive value for postoperative RFS in NMIBC patients. Abstract : The recurrence‐free survival (RFS) rates of the high neutrophil hemoglobin product to lymphocyte ratio (NHL) group and the low NHL group were 54.0% and 75.9%, respectively, with significant difference between the two groups ( p < 0.001), NHL have certain predictive value for postoperative RFS in non‐muscular invasive bladder cancer patients.